THE SPECIFIC FEATURES OF THE PERFORMANCE OF NOTARIAL ACTIVITIES BY CONSULAR INSTITUTIONS OF UKRAINE: THEORETICAL AND LEGAL ANALYSIS - Мачуська, Ірина; Тітова, Валентина; Недільченко, Світлана; Аргатюк, Ірина (SWorldJournal, 2025)
The article examines the peculiarity of the performance of notarial acts by consular institutions and diplomatic missions of Ukraine. It is noted that diplomatic missions and consular institutions of Ukraine abroad are permanent institutions of Ukraine, t